2008
DOI: 10.1007/s12064-008-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

A self-referential model for the formation of the genetic code

Abstract: A model for the formation of the genetic code is presented where protein synthesis is directed initially by tRNA dimers. Proteins that are resistant to degradation and efficient RNA-binders protect the RNAs. Replication becomes elongational producing poly-tRNAs from which the mRNAs and ribosomes are derived. Attributions are successively fixed to tRNAs paired through the perfect palindromic anticodons, with the same bases at the extremities (5'ANA: UNU 3'; GNG: CNC; principal dinucleotides, pDiN). The 5' degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…These authors concluded that "the evolution of the genetic code, translation, and cellular organization itself follows a dynamic whose mode is, if anything, Lamarckian" (Vetsigian et al 2006). Another interesting non-Darwinian model for the evolution of the genetic code is the SelfReferential (SR) model (Guimarãez et al 2008a(Guimarãez et al , 2008b. This model regards the code as a consequence of the existence of proto-tRNAs, small prebiotic tRNA-like molecules: tRNA-like in the sense of having the ability to form dimers by base-pairing (through their proto-anticodons) and to receive the addition of other molecules to one end.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors concluded that "the evolution of the genetic code, translation, and cellular organization itself follows a dynamic whose mode is, if anything, Lamarckian" (Vetsigian et al 2006). Another interesting non-Darwinian model for the evolution of the genetic code is the SelfReferential (SR) model (Guimarãez et al 2008a(Guimarãez et al , 2008b. This model regards the code as a consequence of the existence of proto-tRNAs, small prebiotic tRNA-like molecules: tRNA-like in the sense of having the ability to form dimers by base-pairing (through their proto-anticodons) and to receive the addition of other molecules to one end.…”
Section: Discussionmentioning
confidence: 99%
“…"Eventually this collection of eclectic and changeable cells coalesced into the three basic domains known today" (Woese 1968). In the SR model (Guimarãez et al 2008a(Guimarãez et al , 2008b, protein functions should also feedback positively upon the nucleic acids, thereby providing for a double link between genes and proteins, and both links being of equal weight. Therefore, in the SR model it does not make sense the idea of "selfish genes" or "selfish proteins."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-referential (SR) process, of protein products looping back to stabilize and stimulate the nucleic acids -producers, thereafter memories in RNPs -has already received contributions from diverse sources, beyond the proposition of the model (SRM) [108,109]. Ribosomal proteins belong to the category of Intrinsically Disordered [42], which is a character of the early encodings in the SRM.…”
Section: Metabolic Perspectivesmentioning
confidence: 99%
“…The self-referential (SR) process, of protein products looping back to stabilize and stimulate the nucleic acids -producers, thereafter memories in RNPs -has already received contributions from diverse sources, beyond the proposition of the model (SRM) [93,94]. Ribosomal proteins belong to the category of Intrinsically Disordered [35], which is a character of the early encodings in the SRM.…”
Section: Metabolic Perspectivesmentioning
confidence: 99%